(untitled) (Web of Teachers: Inderscience Research, 2025)
The article will talk about the importance of interdisciplinary integration in the teaching of the science of Electrical Engineering and the basics of electronics at a higher military educational institution. The areas of interdisciplinary integration that need to be considered are outlined. The areas of interdisciplinary integration that need to be considered are outlined. Concepts related to integration have been analyzed.